Variabel-Variabel yang Memengaruhi Status Partisipasi Pendidikan Prasekolah di Pulau Sumatera Tahun 2021 - Nugroho, Guntur; Setiadi, Yaya (Seminar Nasional Official Statistics, 2023)
In 2021, all provinces in Sumatera had a lower early childhood education gross enrollment rate achievement compared to the national level, and the achievements varied among the districts/cities within them. This indicates that preschool participation in Sumatera is still low and uneven. However, the supporting infrastructure for preschool education in Sumatera is relatively adequate compared to other islands. The aim of this study is to determine the variables at individual and district/city level that significantly influence preschool education participation status in Sumatera, along with the magnitude of their influence. The analytical method used is multilevel binary probit regression. The results found that variables such as child's gender, child's age, classification of residence, household per capita expenditure quintile, household size, mother's internet usage status, mother's highest education level, and teacher-to-child ratio for children aged 3-6 years have a significant influence on the preschool education participation status in Sumatera Island in 2021.